2015
DOI: 10.1002/jcp.25094
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol Inhibits Cannabinoid CB1 Receptor Gene Expression in 3T3‐L1 Preadipocyte Cell Line

Abstract: The 3T3-L1 preadipocyte cell line is a well characterized cell model for studying the adipocyte status and the molecular mechanisms involved in differentiation of these cells. 3T3-L1 preadipocytes have the ability to synthesize and degrade endocannabinoid anandamide (AEA) and their differentiation into adipocytes increases the expression of cannabinoid (CB1) and PPAR-γ receptors. Clinically, the blocking stimulation of the endocannabinoid pathway has been one of the first approaches proposed to counteract the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…The decrease in WAT fasn mRNA levels produced by HT treatment was accompanied by a reduction in plasma TAG levels, possibly due to the antagonist effect of this compound on the PPARγ signaling pathway. In agreement with our results, some mammal studies have demonstrated that CA and HT regulate WAT mass by suppressing lipogenic enzyme activity and claimed that PPARγ antagonists can be used to treat hyperlipidemia [74,75]. Interestingly, HT also downregulated pnpla2 transcript abundance in rainbow trout WAT, which is indicative of decreased lipolysis, leading to a reduction in lipid turnover or compensation for excessive WAT decrease.…”
Section: Discussionsupporting
confidence: 91%
“…The decrease in WAT fasn mRNA levels produced by HT treatment was accompanied by a reduction in plasma TAG levels, possibly due to the antagonist effect of this compound on the PPARγ signaling pathway. In agreement with our results, some mammal studies have demonstrated that CA and HT regulate WAT mass by suppressing lipogenic enzyme activity and claimed that PPARγ antagonists can be used to treat hyperlipidemia [74,75]. Interestingly, HT also downregulated pnpla2 transcript abundance in rainbow trout WAT, which is indicative of decreased lipolysis, leading to a reduction in lipid turnover or compensation for excessive WAT decrease.…”
Section: Discussionsupporting
confidence: 91%
“…It has been suggested that oleuropein may alter catecholamine synthesis in the brain [47]. On the other hand, it has been reported that hydroxytyrosol, another antioxidant substance extracted from olive leaves, may affect the endocannabinoid system by inhibition of its receptors (CB1) [12]. The endocananabonoid system is not only involved in energy regulation in the organism as a metabolic signaling system, but also in the stress response [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that it activates glucose consumption in a dose-dependent manner in adipocytes and in myotubes [10], and may reduce lipid levels by suppressing lipid synthesis and promoting fatty acid oxidation via the regulation of adenosine monophosphate-activated protein kinase (AMPK) [11]. Recently, it has been reported that olive extracts may modulate cannabinoid receptor (CB1) gene expression, which regulates energy homeostasis in the organism [12]. Due to its effects shown on glucose uptake and lipid metabolism, its use by dietary interventions might affect a specific fatty acid mobilization and glycogen stores as well as amino acid utilization [13]; however, there is no information on the specific mobilization of the fatty acid or free amino acid profile prior to slaughter in fasting conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, 3T3-L1 cells have been extensively over the last five years to evaluate the effects of compounds or nutrients on adipogenesis, to establish the underlying molecular mechanisms of adipogenesis and to evaluate the potential application of various compounds and nutrients in the treatment of obesity [ 30 , 31 , 32 ]. Particularly, compounds such as quercetin [ 33 , 34 ] and resveratrol [ 35 , 36 ] inhibit adipogenesis in 3T3-L1 adipocytes.…”
Section: Animal Cell Modelsmentioning
confidence: 99%